Condition and productivity of planted oak stands in the Left-Bank Forest-Steppe of Ukraine - Ткач , В. П.; Румянцев , М. Г. (Forestry and Forest Melioration, 2022)
Introduction The state of planted oak stands in the Left-Bank Forest-Steppe was assessed a long time ago. Meanwhile, forest stands are constantly undergoing the influence of various abiotic, biotic, and anthropogenic factors. Therefore, it is necessary to carry out a quantitative assessment of their state. It will enable predicting the processes of decline in stands as well as developing and improving forestry measures aimed at strengthening their resilience, enhancing both their productivity and ecological functions. These matters are also relevant for the planted oak forests in the Left-Bank Forest-Steppe of Ukraine. The aim of the study was to determine the current state and productivity of the planted oak (Quercus robur L.) stands in the Left-Bank Forest-Steppe. Materials and Methods Forest management materials (as of 01.01.2011) served as the basis for determining the forestry and mensuration indicators of the planted oak stands of the Left-Bank Forest-Steppe. In total, about 40.000 plots were analysed. The area of the studied stands made 101.3 thousand hectares. The obtained materials were used to analyse the productivity of pure and mixed modal oak stands. The health condition of the oak trees was assessed at 33 sample plots laid out according to the generally accepted forestry and forest mensuration methods. These plots were established in planted oak stands of different ages and compositions. The stands grow in the fresh maple-lime forest site conditions (Kharkiv region, Kharkiv Forest Research Station). No forestry activities were carried out there during the last 10 years. To define the health condition of the trees, we applied the scale of the condition categories given in the Sanitary Forests Regulations in Ukraine. The state of oak stands was described with a weighted average state index. Results The obtained findings indicate that the total area of the planted oak stands in the forest fund of the Left-Bank Forest-Steppe enterprises managed by the State Forest Resources Agency of Ukraine made 101.3 thousand hectares or almost 36% of the total area of the oak forests. By their functional purposes, the studied oak stands are classified as commercial forests, protective ones, forests of nature protection, scientific, historical and cultural purposes, recreational and health-improving forests. The results of the study show that the mixed planted oak stands with optimal composition have slightly higher productivity compared to the stands with a pure composition. Thus, at the age of 90–100 years, the stock of the pure modal oak stands is lower on average by 6% compared to the mixed ones. It indicates that the planted oak stands use their forest site capacity insufficiently. The average index of health condition in the studied oak stands of different ages and compositions ranges from 1.69 to 2.45 points. There is a clear tendency for a decrease in the share of trees of age categories 1 and 2 among both pure and mixed stands, and an increase in the share of trees of categories 3 and 4, as well as categories 5 and 6. However, in mixed stands, this tendency is less pronounced than in pure stands. The share of dead standing trees in the total stock of oak stands is low and ranges from 2% to 6%. At that, trees affected by forest pathogens predominate in the dead wood. Conclusions The planted oak forests in the Left-Bank Forest-Steppe of Ukraine perform vital ecological and protective functions and are of great national economic importance. However, their age structure is unbalanced and thus, it does not promote the idea of sustainable development of forestry. Large areas are occupied by pure stands, which are characterized by lower productivity and worse health condition compared to mixed stands. The study showed that the condition of pure oak stands is deteriorating with age increase in the range of 75–85 years. The stock of modal mixed stands at the age of 90–100 exceeds the stock of pure oak stands on average by 6%. We came to the conclusion that in order to significantly improve the general condition of planted oak forests, it is necessary to take a number of measures, in particular, related to clarifying the age of maturity of stands, revising at that the division of forests according to their functional purpose, etc. It is also necessary to timely carry out appropriate tending felling and sanitary felling in the stands. Moreover, it is advisable to start landscape felling in the forests of green areas. 2 Fig., 3 Tables, 18 Refs.